MODEL PEMBELAJARAN INTEGRATIF AGAMA DAN SAINS DI MADRASAH IBTIDAIYA NEGERI 2 KUBU RAYA - Salito (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is based on the idea that the implementation of education in madrasas is currently no different from the implementation of education in schools. If previously education in madrasas was a continuation or at least an adoption of the pesantren education system which was strong with religious lessons, then at this time the superiority of these religious values, was uprooted in the implementation of education in madrasas, in this study a research and development (R&D) model was used. In addition, data collection is also complemented by observation, and interviews with teachers and students during the learning process. While the results of this study are integrative learning models in madrasah ibtidaiyah, by integrating science subjects with religion, Fiqh, SKI, Akidah Akhlak, Quran Hadith subjects can be integrated with Mathematics, Science, Social Studies subjects so that the learning process is more meaningful. This integrative model connects several disciplines into one learning activity. Keywords: Integrative Learning Model, Science and Religion